MENGEMBANGKAN PANDUAN TUGAS PENELITIAN MINI UNTUK SISWA SEMESTER PERTAMA YANG MENDAFTAR DI UNIVERSITAS NEGERI MEDAN - Rahmulyani Rahmulyani; Nasrun Nasrun; Zuraida Zuraida; Nani Barorah Nasution; Nindya Ayu Pristanti; Miswanto Miswanto (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
The objectives of this study is the availability of standardized mini research assignment manuals for the student development subject as University courses that must be taken by all students in the first semester in all the Faculty in Medan State University. This research is a development research following the Borg and Gall models. Data collection techniques using a questionnaire that previously analyze by material and media experts. The trial questionnaire was given to 50 students of first semester of Mathematics Department and operational trials were given to 150 students who came from various majors such as the Department of Physics, Chemical Economics, Geography, Mechanical Engineering and Electrical Engineering with random sampling techniques. Data analysis techniques using quantitative descriptive analysis. The outputs of this research is the mini research task handbook for student development subjects for first semester students of Medan State University.Keywords: Mini Research, Guiding Book, Technology and Science.